Kecerdasan Emosional Tokoh Perempuan Muslimah dalam Novel Assalamualaikum Beijing Karya Asma Nadia - Galuh Dilah; Azizatuz Zahro' (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2021)
This study is intended to describe the intelligence of emotional, that the main character has in the novel entitled “Assalamualaikum Beijing” by Asma Nadia. This study used qualitative approach with the study of literary psychology. The qualitative approach using the study of literary psychology is chosen because this study is meant to describe the phenomena in form of words and language regarding the mental aspects of the main character. A type and method of this study were using document study and content analysis. This study belonged to the document study because the researcher was reviewing the written document in the form of a novel entitled “Assalamualaikum Beijing” by Asma Nadia. The data analysis is done by presenting the data, interpreting the data, and drawing the conclution. The results of this study showed that the emotional intelligence of the Muslim women in the novel covered (1) the ability of managing the emotions, (2) the ability of motivating herself, and (3) the ability of building relationship. The ability to manage emotions in the form of the ability to control impulses and overcome anxiety and sadness. The ability to motivate themselves in the form of a character's desire to succeed and take advantage of other situations, obstacles, and self-problems as motivation. The ability to build relationships is demonstrated through the interaction of characters in creating close relationships, maintaining relationships, building comfort and moving others.